Classroom Evaluation of Deep Learning: Effects on Reading Comprehension among Seventh Graders in Indonesia - Rozanah Katrina Herda; Margana Margana; Binar Winantaka; Jeffri Dian Andika; Syafruddin Syafruddin; Fauziyyah Mufida Suni; Mutiara Angelina Octavia Subekti; Bazilah Raihan Mat Shawal (Wahana Pendidikan, 2026)
In Indonesian instructional design, the principles of mindful, meaningful, and joyful learning have guided efforts to create engaging learning experiences in a deep learning nuance. Building on this foundation, deep learning has been increasingly recognized for its potential to strengthen students’ comprehension skills. This study assesses the effectiveness of a deep learning approach in enhancing reading comprehension among seventh-grade students in Indonesia and examines students’ perspectives on learning. Employing a quasi-experimental one-group pretest–posttest design, the study was conducted at a state junior high school with 32 students and included quantitative data from pretests and posttests, followed by qualitative data from semi-structured interviews with students and teachers. The quantitative results showed a significant improvement in reading comprehension, indicating that the deep learning approach effectively enhanced students’ reading performance. Qualitative findings supported this outcome, revealing increased student confidence and participation. These findings suggest that structured deep learning activities, combined with a supportive environment, foster greater student engagement and reading comprehension.